(untitled) (Studia austriaca, 2012)
Eva Rossmann’s mystery novel Russen kommen, the tenth in a popular series, takes up a hot topic in Austria’s tourism industry: the tensions surrounding the recent influx of newly rich Russian visitors. This article uses Rossmann’s mystery as a case study to examine the impact of global culture and transnational investments on Austrian society. Trapped between provincialism and globalization, Austrians are forced to revisit old fears and find new ways of dealing with contemporary challenges. Due to its wide appeal, popular culture can lead the way in these negotiations.